Cerebral dysautonomy as a clinical repercussion in children with traumatic brain injury - Jassiara Soares da Silva (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: Dysautonomia or Paroxysmal Sympathetic Hyperactivity (PSH) affects more than 50% of patients suffering from severe traumatic brain injury (TBI), which is a major cause of morbidity and mortality in children under 12 years. The goal is to demonstrate that PSH is established as a consequence in children with severe brain trauma.